An interactive fuzzy programming approach for a sustainable supplier selection under textile supply chain management. (May 2021) - Tayyab, Muhammad; Sarkar, Biswajit
Graphical abstract: Highlights: Dyestuff supplier evaluation is a critical phase for textile SMEs. Interactive fuzzy approach is applied to control uncertainty. Individual attributes of expert committee are gauged. Government participation in dyestuff regulation is promoted. An integrated supplier selection and transportation model is presented. Abstract: Textile dyestuff supplier evaluation and quantity allocation is a multi-period multi-objective optimization problem of a business triad comprising of cost, quality, and time. To date, no such sufficing textile supply chain management model is reported that optimizes all three components of the business triad along with customer complaints and external quality audit. This research work initiates an advanced integrated multi-dimensional evaluation approach to support small and medium-sized textile industries in effective supplier selection and quantity allocation. Many small and medium-sized enterprises in the textile sector have little or no facilities to evaluate the quality of incoming dyes in their premises. An intervention of government laboratories is recommended in this study, which play a compelling role to regulate and help evaluate the dyestuff suppliers according to the acceptable quality limit. A multi-period multi-objective textile supply chain management (MPMOTSCM) model is developed for simultaneous achievement of supplier evaluation and order allocation. Based on the recommended business triad and expert committee input, an interactive weighted fuzzy goal programming model is developed. A numerical assessment using metaheuristic approach is carried out to elaborate the practical applicability of the model. The experimental outcomes show that the proposed model has achieved 45.77% satisfaction level for the cost, 80.73% for the quality, and 95.04% for the time. Analysis of the model indicates that this model provides a robust decision support system to the managers for dyestuff supplier evaluation, selection, and quantity allocation.